Utilizing Prolog for Automatic Transformation of English Words - Barkah, Nida Muhliya; Siregar, Maria Ulfah (Journal of Information Technology and Cyber Security, 2024)
Artificial Intelligence is a branch of computer science that focuses on developing systems that emulate human intelligence to execute commands or tasks by applying the concept of automatic reasoning. Automatic reasoning is the ability of a system to draw logical conclusions, make decisions, and solve problems independently, without human intervention, based on provided information or rules. The complexity of grammatical rules in English often causes difficulties in understanding and remembering them, hindering mastery of correct English structures. To address these challenges, this research uses automatic reasoning as the primary foundation for developing automatic transformation systems for English words—specifically, transforming singular nouns into plural forms and adjectives into adverbs of manner. The objective of this research is to apply grammatical rules during word transformation in Prolog. Furthermore, this study tests the effectiveness and accuracy of the process by evaluating the success rate of correct transformations. The system's performance is assessed by comparing the transformed words to their correct plural forms and corresponding adverbs of manner, based on predefined grammatical rules. This research does not involve participants directly but evaluates the system's performance on a set of predefined words. The results demonstrate that the system successfully transformed all tested words with 100% accuracy, effectively altering their structure. This indicates that the system is both effective and reliable for use in English language learning. Additionally, the system's high accuracy in handling various morphological transformations makes it a valuable tool for improving English grammar and writing skills.